Spatial Patterns and Scaling Distributions of Earthquake-Induced Landslides—A Case Study of Landslides in Watersheds Along Dujiangyan–Wenchuan Highway - Liu, Xuemei; Su, Pengcheng; Li, Yong; Xu, Rui; Zhang, Jun; Yang, Taiqiang; Guo, Xiaojun; Jiang, Ning (Frontiers in Earth Science, 2021)
Earthquake-induced landslide has various spatial characteristics that can be effectively described with the frequency-area curve. Nevertheless, the widely -used power-law curve does not reflect well the spatial features of the distribution and the power exponent does not show the association with the background factors. There is a lack of standards for building the relationship and its implication on the spatial distribution of landslides has never been analyzed. In this study, we propose a new form of frequency distribution and explore the parameters in the typical watersheds along the highway from Dujiangyan to Wenchuan (DW) in the Wenchuan earthquake region. The obtained parameters are related to the landslide density and proportions of the large-scale landslides. Furthermore, a hot spot analysis of landslides in the watersheds is conducted in order to assess the relationship between the parameters and the spatial cluster patterns of landslides. The hot spots highlight the size and distance of landslide areas that cluster together, while the distribution parameters reflect the density and proportions of landslides. This research introduces a new method to analyze the distribution of landslides and its association with the spatial features, which can be applied to the landslide distribution in relation to other influential factors.